157k views
4 votes
15 - 4x = 6 - 3x

whats the answer. ​

1 Answer

5 votes

Answer:9

Step-by-step explanation: First you add the 3x to both sides(the -4x and the -3x) and then you get 15-1x=6. Next you subtract 15 from 15 and 6, so you get -1x=-9. So then you divide both sides by -1 (do -1x over -1 equals -9 over -1). Last you do the dividing and you get x=9.

User Smitkpatel
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.